The Difficulty of Saying "I": Translation and Censorship of Christa Wolf's Der geteilte Himmel - Katharina von Ankum (Studies in 20th & 21st Century Literature, 1993)
The end of the GDR in 1990 triggered a vivid literary debate in Germany which focused on the interrelationship of politics, literature, and criticism. In this context, the work of Christa Wolf was attacked as primary example of self-censorship and collaboration. In my article, I argue that Wolf became the target of literary criticism largely because of her attempt to express female subjectivity in her texts. In my contrastive analysis of Der geteilte Himmel (1963) and its English translation (1965), I read Wolf's text as an initial attempt at a "socialist modernism." The continued value of this and subsequent works by Wolf lies in the accuracy and complexity with which she probes human behavior under adverse historical circumstances. Even a text like Der geteilte Himmel, which on a surface level reads merely like a political vote for socialism in the GDR as well as the writer's support for the division of Germany, eludes the binary opposition of East/West, them/us that critics have used to categorize Wolf's work. The hybrid nature of the text serves as example of Wolf's sincerity as a writer, evidence of her personal integrity, as well as her relentless commitment to a social alternative.
Keywords: GDR; 1990s; 1990; Christa Wolf; literary debate; interrelationship; politics; literature; criticism; attacked; self-censorship; collaboration; express female subjectivity; female subjectivity; Der geteilte Himmel; English translation; Divided Heaven; socialist modernism; human behavior; adverse historical circumstances; socialism; DDR; political vote; division of Germany; binary opposition; East; West; East/West; them/us; social alternative; hybrid